1989
DOI: 10.2307/1130797
|View full text |Cite
|
Sign up to set email alerts
|

Age versus Schooling Effects on Intelligence Development

Abstract: The effect of formal education, as opposed to chronological age, on intelligence development has suffered from inadequate empirical investigation. Most studies of this issue have relied on natural variation in exposure to school among children of the same age, thus confounding differences in schooling with differences in other intelligence-related variables. This difficulty can be overcome by a quasi-experimental paradigm involving comparison between children who differ in both chronological age and schooling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(97 citation statements)
references
References 13 publications
5
91
0
1
Order By: Relevance
“…In conclusion, the results are compatible with the ones found in literature in the field (Ackerman, 1996;Cahan & Cohen, 1989;Cahan & Noyman, 2001;Ceci, 1991;Gustafsson, 2001;McGrew & Evans 2002;Stelzl et al, 1995), thus corroborating in part the interpretations of the specific factors involved in the BRT-5 sub-tests. These findings follow the logic of construct validity research, as delineated by Cronbach and Meehl (1955), whose study demonstrates a correspondence between a nomological network of relationships between constructs defined by theoretical and empirical studies in literature and the network of empirical correlations found between the observed variables that supposedly measure such constructs.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, the results are compatible with the ones found in literature in the field (Ackerman, 1996;Cahan & Cohen, 1989;Cahan & Noyman, 2001;Ceci, 1991;Gustafsson, 2001;McGrew & Evans 2002;Stelzl et al, 1995), thus corroborating in part the interpretations of the specific factors involved in the BRT-5 sub-tests. These findings follow the logic of construct validity research, as delineated by Cronbach and Meehl (1955), whose study demonstrates a correspondence between a nomological network of relationships between constructs defined by theoretical and empirical studies in literature and the network of empirical correlations found between the observed variables that supposedly measure such constructs.…”
Section: Discussionsupporting
confidence: 90%
“…By eliminating 12 of the easiest problems, in which performance in a college sample is near ceiling (Carpenter et al, 1990;Raven, Court, & Raven, 1977), and 6 of the most difficult problems, in which performance is nearly floored (Carpenter et al, 1990;Raven et al, 1977), we tried to achieve a cut-time version of the Advanced Progressive Matrices that would still have adequate reliability and discriminating power. A previous investigation used a 16-item version of the Standard Progressive Matrices for cut-time administration and achieved reliabilities over .75 in samples of children (Cahan & Cohen, 1989). The split-half reliability of our 18-item measure (.79, SpearmanBrown corrected) was similar.…”
Section: Cognitive Tasksmentioning
confidence: 53%
“…Table 2 shows the raw correlations between measures (below the diagonal), reliabilities of the measures calculated as Chronbach's Alpha across trial subsets (in bold, on the diagonal), and correlations with age group variance partialled out (above the diagonal). Age group based on year in school was used as a developmental variable in the correlations rather than age in months because of evidence that it is a stronger predictor of scholastic skills (Bentin, Hammer, & Cahan, 1991;Cahan & Cohen, 1989). It can be seen that the measures were fairly reliable and all of the correlations were significant.…”
Section: Means and Age Effectsmentioning
confidence: 99%